Afrocentrism mythical pasts and imagined homes - Howe, Stephen (London Verso, 1998)
In this provocative study, Stephen Howe traces the sources and ancestries of the movement, and closely analyses the writings of its leading proponents including Molefi Asante and the legendary Senegalese historian Cheikh Anta Diop. Martin Bernal?s contribution is also assessed. Hard-hitting yet subtle and scholarly in its appraisal of Afrocentric ideas, and based on wide-ranging research in the histories both of Afro-America and of Africa itself, Afrocentrism not only demolishes the mythical ?history? taught by black ultra-nationalists but suggests paths towards a true historical consciousness of Africa and its diaspora.
Includes index
Keywords: Pan Africanism